Register dalam Berkebun Tanaman Hias: Kajian Struktur dan Makna - ARI NUGRAHANI; ENDANG SETYOWATI; ENDANG SUMARTI (Universitas Insan Budi Utomo, 2024)
This article comes from the phenomenon of new habits of the community since COVID-19 has changed a number of activities, one of which is gardening activities. This new habit is an activity at home during the WFH season and continues to this day. The rise of the sale of ornamental plants, both online and offline, has made the world of trade more vibrant. Impromptu planters have sprung up, as well as terms related to ornamental plants, types, and care. This certainly makes new planters a little confused and not used to it. Local, national, and foreign terms also enrich the treasure of ornamental planting knowledge. This research is aims to bridge the confusion about the terms so that people able to easily understand and use them in their daily lives. Through a linguistic descriptive approach, popular terms regarding ornamental plants are grouped according to their meaning field. The search for meaning was carried out in stages, both through online dictionaries of ornamental plants and through interviews, and using the introspection method to dig up data. Interviews with ornamental plant traders and collectors were conducted for follow-up searches for meaning. This strategy is equivalent to a directed fishing technique and taking notes. Data was also collected from social media, YouTube, and Instagram plantsellers who focused on the ornamental plant business. The results of this study have a reference meaning contained in gardening ornamental plants, namely a reference meaning that refers to gardening tools, containers or planting places, plant watering conditions, gardening activities, plant location, plant character, plant growing process, planting media, plant pests, plant drugs/fertilizers, plant conditions, plant types, and planting techniques.